Pengaruh pengawasan preventif dan pengawasan detektif terhadap efektifitas pengendalian anggaran (studi empiris pada satuan kerja perangkat daerah di kabupaten kampar) - Julio Herdi Peuranda; Raja Adri Satriawan; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is conducted to analyze the influence of effectiveness of budget control to echelon III and IV in SKPD Kampar regency. The research consists of a dependent variable that is effectiveness of budget control (Y) and two independent variables which preventive (X1) and detective control (X2).The population in this research is all of echelon III and IV officials in SKPD Kampar regency with eightyeight respondents using purposive sampling technique. Data analysis using quantitative method with SPSS version seventeen.The result of this research convey that all of the independent variables simultaneously affect the effectiveness of budget control significantly. At partially test only detective control has effect significantly while the others independent variables affect not significantly. Adjusted R square show at moderate level (fifty one point three percent). It means fourty eight point seven percent has affect by other variable beyond this research.Keywords: Preventive and detective control, effectiveness of budget control